Antimicrobial activity of water-soluble triazole phenazine clickamers against E. coli - Hayden, Steven C.; Bryant, Jonathan; Mackey, Megan A.; Höfer, Katharina; Lindner, Benjamin; Nguyen, Vanessa P.; Jäschke, Andres; Bunz, Uwe H. F. (Chemistry - a European journal, 2014)
The antimicrobial potency of phenazine derivatives is attenuated by their inherently hydrophobic nature, complicating their use as antibiotic drugs. We have analyzed the cytotoxicity and mode of action of water-soluble bis-triazolyl phenazines against E. coli and a human epithelial (HaCat) cell line. We observed complete inhibition of bacterial growth over concentration ranges that do not affect the viability of human epithelial cells. Confocal fluorescence microscopy revealed a high degree of interaction between the phenazine compounds and E. coli, as well as evidence of membrane damage in phenazine-treated E. coli. Additional data suggests that the potency of these particular water-soluble phenazine compounds does not result from the production of reactive oxygen species, but rather from cytotoxic interference with metabolic electron-transfer cascades.